Learning Method in the Covid-19 Pandemic Era: Systematic Review - Sumarliyah, Eni; Rofiqi, Erfan; Hamsia, Waode (STRADA : Jurnal Ilmiah Kesehatan, 2021)
A Covid 19 pandemic still haunts people around the world. The purpose of this research analysed learning methods that can be done during the pandemic. The research design used a systematic review. Search for articles was carried out from September to December 2020 by accessing 5 electronic databases Scopus, Science direct, Pubmed, Ebscohost and Proquest. The keywords based on MeSH according to the topic determined by the researcher. To assess the quality of researches that the researchers used the JBI Critical Apparitional Tool and PRISMA checklist as a guide for screening articles. Total of 11 articles were reviewed with a JBI score of> 50%. The results of the article analysis obtained, data was obtained that online learning methods are the main choice during the pandemic, namely by online learning using applications and e-learning, virtual and online simulations. This method is able to provide good effectiveness and is the main choice.